2002
DOI: 10.1051/apido:2002030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ingestion of a biotin-binding protein on adult and larval honey bees

Abstract: -The insecticidal properties of biotin-binding proteins (BBPs) have recently been exploited in transgenic plants. As BBPs have a broad spectrum of insect toxicity, their potential impacts on non-target insects such as honey bees need to be assessed. In this study, the effects of feeding a purified BBP, avidin, to honey bee larvae and adults were determined. A realistic larval dosing regime was developed by estimating the pollen content of brood food in the field and adding avidin to artificial diet at rates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Measurements of acinus diameter, gland mass and protein content of the glands suggested that aprotinin, avidin and Cry1Ba, if present in transgenic pollen at the concentrations tested here, are extremely unlikely to have a marked effect on hypopharyngeal gland development. For the biotin-binding protein and the Bt toxin, this is in accord with earlier reports of no impacts on bees (Sims, 1995;Arpaia, 1996;Malone et al, 1999Malone et al, , 2002b.…”
Section: Discussionsupporting
confidence: 89%
“…Measurements of acinus diameter, gland mass and protein content of the glands suggested that aprotinin, avidin and Cry1Ba, if present in transgenic pollen at the concentrations tested here, are extremely unlikely to have a marked effect on hypopharyngeal gland development. For the biotin-binding protein and the Bt toxin, this is in accord with earlier reports of no impacts on bees (Sims, 1995;Arpaia, 1996;Malone et al, 1999Malone et al, , 2002b.…”
Section: Discussionsupporting
confidence: 89%
“…Some new tests have been proposed to estimate the larvae exposure. Among them, field (Oomen et al, 1992) and semi-field (Leyman et al, 1999;Tornier, 1999) tests do not appear appropriate since larval exposure cannot be controlled, whereas laboratory tests (Malone et al, 2002;Brødsgaard et al, 2003) might be used to estimate adequately the larvae exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of imidacloprid consumed by honeybees is determined by the following equivalence: 1 mg of sugar contained in nectar or honey = 4.75 pg of imidacloprid and 1 mg of pollen = 3.4 pg of imidacloprid in nectar and pollen coming from Gaucho ® seed-dressed plants. N Larvae consume royal jelly, produced by nurses, which contains honey and pollen (Haydak, 1943(Haydak, , 1968(Haydak, , 1970Kunert and Crailsheim, 1988;Malone et al, 2002).…”
Section: Nectar and Pollen Consumptionmentioning
confidence: 99%
“…However, as proteinase inhibitors are known to be extremely stable (as with pancreatic trypsin inhibitors found in mammals), is possible that PIs will be passed to the larvae with the larval jelly. However, if GM products only reach the larval food through modified pollen, the average amount of GM product in larval food in bee colonies would be between 0.1% and 0.2% if the pollen express 1% PI of total protein (calculation based on Wille et al, 1985 andMalone et al, 2002). Therefore, we chose 0.1% and 1.0% SBTI of total soluble protein as realistic low and high expression levels, respectively , and investigated the juvenile development, mortality, and adult body mass with larval diets containing 0.1% or 1.0% (w:w) SBTI of total protein.…”
Section: Methodsmentioning
confidence: 99%